Hypothyroidism in type 2 diabetics – a hospital-based prevalence study - Narukurthi, Ravi Kiran; Radha Mani, Dr. C (Mandava); Ala, Deepthi; Chandra, T Jaya (International Journal of Medical Research and Review, 2020)
Introduction: Thyroid hormones and insulin are the antagonists and both are involved in cellular metabolism. With this, the study was planned to find the prevalence of thyroid dysfunction in type 2 diabetes mellitus (DM). Materials and Methods: Study was conducted in the department of General Medicine, GSL Medical College. The study protocol was approved by the institutional ethical committee. All type 2 diabetics aged >30yrs, irrespective of treatment were included in the study. Individuals on metformin therapy, smokers, thyroid hormone users, who underwent thyroid surgery, individuals on radioiodine therapy, pregnant women and individuals on steroids were excluded. Venous blood samples were taken from for fasting blood glucose and 2-hour post glucose blood sugar, glycosylated hemoglobin, lipid profile, and thyroid function estimated measured by using the autoanalyzer. Chi-square test was used to compare differences in categorical variables and p<0.05 was considered statistically significant. Results: Among 104 participants, 82.7% were euthyroid, 12.5% had subclinical and 4.8% had clinical hypothyroidism; statistically the difference not significant when age/gender was correlated. But there was a significant association with dyslipidemia. Conclusion: Hypothyroidism is very common among type 2 DM individuals and both complement others’ metabolism.